Traditional Tausug Pagkawin in Sulu, Philippines - Sajan, Alkinor R. (Indonesian Community Empowerment Journal, 2021)
In the history of the human race, intimate relationships have been normal. When civilization began to flourish, the norms and standards of societies also thrived and were preserved. copulation is lawfully decreed to be bound by marriage. The marital norm is either prescriptive or proscriptive, depending on the societal standard. The Tausugs claim to be a Muslim tribe. Their marriage custom is traditional, however, but anchored on the Islamic principle where they are obliged to carefully observe the so-called ritual Nikah or pagkawin. Due to the geographical dimensions of the Sulu Archipelago, pagkawin among the Tausugs is of the same concept but slightly different in practice. This literature review aimed to describe the traditional pagkawin and its variations in five different municipalities of Sulu.